2012
DOI: 10.1371/journal.pone.0029317
|View full text |Cite
|
Sign up to set email alerts
|

A Role in Immunity for Arabidopsis Cysteine Protease RD21, the Ortholog of the Tomato Immune Protease C14

Abstract: Secreted papain-like Cys proteases are important players in plant immunity. We previously reported that the C14 protease of tomato is targeted by cystatin-like EPIC proteins that are secreted by the oomycete pathogen Phytophthora infestans (Pinf) during infection. C14 has been under diversifying selection in wild potato species coevolving with Pinf and reduced C14 levels result in enhanced susceptibility for Pinf. Here, we investigated the role C14-EPIC-like interactions in the natural pathosystem of Arabidops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
99
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 42 publications
3
99
2
1
Order By: Relevance
“…Binding of RD21 to AtSerpin1, however, is a mechanism to control RD21's activity as prodeath factor (13,14). Changes in vacuole permeability and protease compartmentalization are supposed to account for this set-point control mechanism (8,14). In support of this model, mutant plants lacking RD21 or overexpressing AtSerpin1 both were found to exhibit significantly less elicitor-stimulated programmed cell death than plants lacking AtSerpin1 (8,13,14).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Binding of RD21 to AtSerpin1, however, is a mechanism to control RD21's activity as prodeath factor (13,14). Changes in vacuole permeability and protease compartmentalization are supposed to account for this set-point control mechanism (8,14). In support of this model, mutant plants lacking RD21 or overexpressing AtSerpin1 both were found to exhibit significantly less elicitor-stimulated programmed cell death than plants lacking AtSerpin1 (8,13,14).…”
Section: Discussionmentioning
confidence: 95%
“…RD21 was originally discovered as a drought-induced gene in A. thaliana (7). Later studies suggested a role in plant immunity and resistance against necrotrophic fungal pathogens such as Botrytis cinerea (8). RD21 has an interesting structure and biosynthetic pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further alignment analysis of their conserved domains showed that both are 83.93% similar in prodomain, 89.25% in protease domain, and 96.49% in granulin domain (data not shown). RD21A is highly overexpressed in the leaf of Arabidopsis particularly during senescence indicating its role in cell death (Shindo et al 2012). Similarly, BrCP3 gene is also remarkably overexpressed in the leaf tissues, about 25-fold higher than in roots and stems of Brassica rapa although the highest levels, 2.48-and 1.39-fold higher than the leaves, were observed respectively in sepal and stamen (Fig.…”
Section: Analysis Ofmentioning
confidence: 86%
“…Reports have been made on papain-like cysteine proteases acting as inhibitory agent against fungus, bacteria, oomycete and nematode such as Rcr3 (Krüger et al 2002), PIP1 (Tian et al 2007), RD19 (Bernoux et al 2008), RD21 (Shindo et al 2012), C14 (Kaschani et al 2010) and Cath B (Gilroy et al 2007). Each has unique participation in the induction of host immunity which is evident in the specific interactions with the effectors, involvement in a specific molecular battlefield, and the resulting immunity threshold (Niño et al 2014).…”
Section: Introductionmentioning
confidence: 99%